Chikungunya Patient presented with Arthritis: A Case Report - Hassan, Mohammad Sayeed; Sonia, Sheikh Farjana; Yusuf, Mohammad Abdullah; Ara, Ferdous; Sharif, Ahmad Raihan; Ahmed, Farid; Rahman, Md. Atiqur (Journal of Current and Advance Medical Research, 2014)
Chikungunya is an arthropod borne viral disease considered as the new emerging infectious disease in many countries of Asia, Africa, Europe and America. In this present case report a 45 year old lady was presented with multiple joint pains following exanthematous febrile illness. Laboratory result revealed this case as positive for chikungunya. DOI: http://dx.doi.org/10.3329/jcamr.v1i1.19562 J Curr Adv Med Res 2014;1(1):21-22